Case Report: Low-grade glioma with NF1 loss of function mimicking diffuse intrinsic pontine glioma - Bernstock, Joshua D.; Karandikar, Paramesh V.; Chen, Jason A.; Seidlitz, Jakob; Friedman, Gregory K.; Meredith, David M.; Liu, Kevin X.; Haas-Kogan, Daphne; Reardon, David A.; Peruzzi, Pier Paolo (Frontiers in Surgery, 2024)
Intrinsic, expansile pontine tumors typically occur in the pediatric population. As such, these tumors characteristically represent diffuse intrinsic pontine glioma (DIPG), now considered a diffuse midline glioma (DMG), H3K27-mutated of the pons. DIPG has limited treatment options and a poor prognosis, and the value of tissue diagnosis from an invasive biopsy has remained controversial. Herein, we present the case of a 19-year-old female with clinical and imaging hallmarks of DIPG, who underwent a biopsy of a tumor in the region of the right middle cerebellar peduncle. Lesional cells were negative for H3K27M alterations and had low-grade histologic features. Next-generation sequencing revealed a frameshift mutation in the NF1 gene as the likely driver mutation. These features suggest a diagnosis of a low-grade glioma related to NF1 loss-of-function, with far-reaching consequences regarding both treatment strategy and prognosis. This case provides support for the utility of diagnostic tissue biopsy in cases of suspected DIPG.